Impact of COVID-19 on food security and cropping patterns in Tajikistan: Evidence from a telephone survey in Khatlon Province - Rajiv, Sharanya; Akramov, Kamiljon T.; Aliev, Jovidon (International Food Policy Research Institute, 2024)
Poor households are the most vulnerable to external shocks. When Kazakhstan and the Russian Federation restricted wheat exports in response to the COVID-19 pandemic, prices for wheat flour and derived products (staple food) increased sharply in Central Asian countries that are dependent on wheat import (the Kyrgyz Republic, Tajikistan, and Uzbekistan). These export restrictions also increased fears of adverse food security outcomes in importing countries. In Tajikistan, these global dynamics translated into significant challenges given its reliance on imports to meet around half of its cereal requirements. The FAO forecasted Tajikistan’s cereal import requirement for 2020/21 at 1,225,000 tons or about 50 percent of its total consumption. Most of this import requirement was made up of wheat, which is a key staple in the Tajik diet, comprising about 54% of total wheat consumption. The country’s key wheat supplier, Kazakhstan, imposed export limitations in April and May 2020. Consequently, despite a good domestic harvest and price stabilization initiatives by the Government of Tajikistan, the domestic price of wheat remained well above the 2019 levels. To unpack the impact of COVID-19 on rural livelihoods and farm decision making, panel data from 1,200 households in Khatlon province in Tajikistan was analyzed. Data was collected through a phone survey in September-October 2020 in 12 districts of Khatlon province, with a set of households previously surveyed in September 2018. The analysis examines respondents’ perceptions of the pandemic’s effects on their households’ livelihoods and agricultural production, disaggregate by 2018 household wealth quartiles. The analysis is descriptive and summarizes respondents’ perceptions. The methodology doesn’t allow us to determine causal pathways or generalize the results beyond Khatlon province.